Administration of Neuropsychological Tests Using Interactive Voice Response Technology in the Elderly: Validation and Limitations - Miller, Delyana I.; Talbot, Vincent; Gagnon, Michèle; Messier, Claude (Frontiers in Neurology, 2013)
Interactive voice response systems (IVR) are computer programs, which interact with people to provide a number of services from business to health care. We examined the ability of an IVR system to administer and score a verbal fluency task (fruits) and the digit span forward and backward in 158 community dwelling people aged between 65 and 92 years of age (full scale IQ of 68 to 134). Only 6 participants could not complete all tasks mostly due to early technical problems in the study. Participants were also administered the WAIS-IV and WMS-IV sub-tests. The IVR system correctly recognized 90% of the fruits in the verbal fluency task and 93-95% of the number sequences in the digit span. The IVR system typically underestimated the performance of participants because of voice recognition errors. In the digit span, these errors led to the erroneous discontinuation of the test: however the correlation between IVR scoring and clinical scoring was still high (93-95%). The correlation between the IVR verbal fluency and the WAIS-IV Similarities sub-test was 0.31. The correlation between the IVR digit span forward and backward and the in-person administration was 0.46. We discuss how valid and useful IVR systems are for neuropsychological testing in the elderly.